2006
DOI: 10.1002/em.20203
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in bone marrow and blood cells of mice exposed to municipal sludge leachates

Abstract: Leachates of municipal solid waste from unsecured disposal sites contaminate sources of potable water and affect human health. In the present study, we have used the Comet assay to evaluate the DNA damage in mice exposed to municipal sludge leachates. Ten percent leachates were prepared from municipal sludge obtained from two different disposal drains. Male Swiss albino mice were treated daily with 0.1-0.4 ml of the leachates by oral gavage for 15 days, and the DNA damage was evaluated in bone marrow and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similar reports by Alimba et al, (2006), Amahdar et al, (2009), Alabi and Bakare (2011) and Alimba et al, (2012) further reported the genotoxic and necrotic effects of leachates obtained from various dump sites. Tewari et al, (2006) reported that DNA damage can occur in bone marrow and blood cells of mice exposed to municipal sludge leachates. Histopathology profiles of the liver was also carried out in order to assess the effects of the varying concentrations of leachates samples on mice due to the significance of the liver as one of the most sensitive predictors of chemical toxicity (Tayeb et al 2010;Alimba et al 2012).…”
mentioning
confidence: 99%
“…Similar reports by Alimba et al, (2006), Amahdar et al, (2009), Alabi and Bakare (2011) and Alimba et al, (2012) further reported the genotoxic and necrotic effects of leachates obtained from various dump sites. Tewari et al, (2006) reported that DNA damage can occur in bone marrow and blood cells of mice exposed to municipal sludge leachates. Histopathology profiles of the liver was also carried out in order to assess the effects of the varying concentrations of leachates samples on mice due to the significance of the liver as one of the most sensitive predictors of chemical toxicity (Tayeb et al 2010;Alimba et al 2012).…”
mentioning
confidence: 99%
“…These include lymphocytes isolated from patients' whole blood. They are exposed to contaminants from environmental matrices also as a result of accidental ingestion and are considered cells to show early signs associated with adverse health effects after exposure to the contaminants [69,70].…”
Section: The Use Of Selected Human Cell Lines In Studies Of the Basal Toxicity Genotoxicity Cytotoxicity And An Estrogenic Potential Of Lmentioning
confidence: 99%
“…The results of dose-response experiments on mice tissues indicated that leachates from municipal sludge can lead to DNA damage (Tewari et al, 2006). The analysis of the municipal sludge leachates showed the presence of cadmium, chromium, copper, nickel lead, zinc and high concentrations of sulfate and nitrate.…”
Section: Wastewater and Sludge Disposalmentioning
confidence: 99%